The osseointegration and stability of dental implants with different surface treatments in animal models: a network meta-analysis - Hao, Chun-Ping; Cao, Nan-Jue; Zhu, Yu-He; Wang, Wei (Scientific reports, 2021)
Dental implants are commonly used to repair missing teeth. The implant surface plays a critical role in promoting osseointegration and implant success. However, little information is available about which implant surface treatment technology best promotes osseointegration and implant stability. The aim of this network meta-analysis was to evaluate the osseointegration and stability of four commonly used dental implants (SLA, SLActive, TiUnite, and Osseotite). The protocol of the current meta-analysis is registered in PROSPERO (International Prospective Register of Systematic Reviews) under the code CRD42020190907 ( https://www.crd.york.ac.uk ). We conducted a systematic review following PRISMA and Cochrane Recommendations. Medline (PubMed), Cochrane Library, Embase, and the Web of Science databases were searched. Only randomized controlled trials were considered. Twelve studies were included in the current network meta-analysis, eleven studies were included concerning the osseointegration effect and five studies were included for stability analysis (four studies were used to assess both stability and osseointegration). Rank possibility shows that the SLActive surface best promoted bone formation at an early healing stage and TiUnite seemed to be the best surface for overall osseointegration. For stability, TiUnite seemed to be the best surface. The present network meta-analysis showed that the SLActive surface has the potential to promote osseointegration at an early stage. The TiUnite surface had the best effect on osseointegration regarding the overall healing period. The TiUnite surface also had the best effect in stability.